2017
DOI: 10.1037/neu0000411
|View full text |Cite
|
Sign up to set email alerts
|

How technology is reshaping cognitive assessment: Lessons from the Framingham Heart Study.

Abstract: Objective This article elucidates how the Boston Process Approach (BPA) can amplify the role of neuropsychology in the study of preclinical and clinical dementia, particularly Alzheimer’s disease (AD), and how advancements in technology expand BPA capacity objectively and exponentially. Method The BPA is based on a conceptualization of cognition as being comprised of multiple processes, the nature of which could not possibly be captured by a single score on a test or battery of tests. Identification of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 108 publications
1
33
0
Order By: Relevance
“…All subjects were evaluated by trained examiners. For those subjects identified as showing symptoms of cognitive decline, dementia diagnosis was reached by consensus of at least one neurologist and one neuropsychologist; the dementia surveillance and diagnostic procedures have been previously outlined in [5, 21]. The entire dataset for all participants was anonymized prior to analysis.…”
Section: Methodsmentioning
confidence: 99%
“…All subjects were evaluated by trained examiners. For those subjects identified as showing symptoms of cognitive decline, dementia diagnosis was reached by consensus of at least one neurologist and one neuropsychologist; the dementia surveillance and diagnostic procedures have been previously outlined in [5, 21]. The entire dataset for all participants was anonymized prior to analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Selection for dementia review is based on whether participants have shown evidence of cognitive decline, as has been previously described. 4…”
Section: Methodsmentioning
confidence: 99%
“…Brain aging research began at FHS in 1976, and the detailed cognitive evaluation methods, case ascertainment procedure, and quality control approaches for FHS have been published [11,12]. Brie y, participants were followed-up approximately every two years in the Original cohort and on average every four years in other cohorts.…”
Section: Assessment and Ascertainment Of Cognitive Statusmentioning
confidence: 99%